Green synthesis of gold nanoparticles reduced and stabilized by squaric acid and supported on cellulose fibers for the catalytic reduction of 4-nitrophenol in water. Issue 94 (23rd September 2016) - Islam, Md. Tariqul; Padilla, Julio E.; Dominguez, Noemi; Alvarado, Daisy C.; Alam, Md Shah; Cooke, Peter; Tecklenburg, Mary M. J.; Noveron, Juan C.
Abstract : Gold nanoparticles reduced and stabilized by sodium squarate in water that attach to cellulose fibers and catalyse the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) with sodium borohydride. Abstract : We report a simple, fast, and green method to produce gold nanoparticles (AuNPs) that are reduced and stabilized by sodium squarate in water and easily attach to cellulose fibers. The AuNPs and its nanocomposites with cellulose fibers exhibited excellent catalytic activity for the reduction of 4-nitrophenol (4-NP) with NaBH4 . A glass column was packed with the nanocomposites and used for the continuous catalytic reduction of 4-NP with NaBH4 and demonstrated to be used multiple times (20×) without loss of catalytic activity.